The use of biologics in children with allergic rhinitis and chronic rhinosinusitis: Current updates - Tan Shinee; Budi Sutikno; Baharudin Abdullah (Wiley, 2019)
Abstract The therapeutic goals of the treatment of allergic rhinitis (AR) and chronic rhinosinusitis (CRS) are symptom relief, avoiding complications, and improving quality of life. In the treatment of AR and CRS, several limitations of currently prescribed medicines have been identified. Antihistamine administration (both oral and topical) together with intranasal corticosteroids bring relief to the majority of patients, but their dependency on the medications and a necessity to maintain strict compliance with regular medication regimes pose a challenge. Immunotherapeutic agents are an option in some patients, but polysensitized patients, the risk of anaphylaxis, and the need for daily administration for years are limiting it from becoming the main therapy modality. Immunotherapy in any form requires commitment by the patient, which renders adherence and compliance issues particularly relevant. The procedure involved are generally time‐consuming and entail an associated risk of severe adverse reactions. The use of biologics could overcome the limitations of other therapeutic modalities. They could be used as a monotherapy or combined with pre‐existing medications. The benefits of targeted therapy include less adverse effects and optimal efficacy. The aim of the present review was to investigate the collective literature to date pertaining to the role of biologics in managing children with AR and CRS.